PENGARUH BRAND IMAGE, BRAND AWARENESS, DAN BRAND TRUST TERHADAP BRAND LOYALTY KONSUMEN PRODUK HIJAB SEGIEMPAT PADA PELANGGAN TOKO BAJU MUSLIM ISTINA BUSANA - Lindara, Noviana (Universitas Nusantara PGRI Kediri, 2023)
This study aims to determine whether customers who purchase quadrilateral hijab goods areloyal to the brand. The study's objective was to examine the impacts of brand awareness, brand trust, and brand image on customers' brand loyalty with quadrilateral hijab products. This study employs survey techniques and a quantitative methodology. The incidental sampling approach was utilized, and there were forty respondents. utilizing several linear regression analysis methods and the data processing software SPSS version 23. The results of the study demonstrate that brand knowledge factors also have a detrimental impact on brand trust and image variables. Future quadrilateral hijab products are anticipated to be able to give brand awareness, brand image, and brand trust greater consideration in order to foster brand loyalty